Experimental Study of Connections with Hardwood Studs - Hudák, J.; Literáti, Zsolt; Kovács, Imre; Radnay, László (International Journal of Engineering and Management Sciences, 2016)
Attitude change is needed in design of timber structures. Truss girder made of timber elements wi th small cross sections can be used on large spans. Constructing structures with the use of these prefabricated trusses reduces the need of in-site work, and makes the use of ti mber structures economic. Rods of truss can be connected with the use of hardwood stud. On this way all steel components can be eliminated from the truss, so it can be used in aggressive environment as well. Dowel type connection, with hard wood stud is the subject of the present research. Hardwood studs were investigated individually and also as the part of separated connections of the truss girder.